Using Agility Exercises For Developing Some Refereeing Skills Of First Class Assistant Referees In Baghdad - Qasem, Sabah; Shakir, Zainab (Journal of Physical Education, 2018)
Using Agility Exercises For Developing Some Refereeing Skills Of First Class Assistant Referees In Baghdad Agility is considered an important motor ability for assistant referees and it is vital for passing modern tests issued in September 2016. The researcher used the experimental method. The subjects were (10) referees; four of them for pilot study. The experimental group followed the exercises designed by the while the controlling group used the traditional exercises followed by the refereeing committee. All referees were tested the standardized agility test issued by the FIFA. The researchers concluded that agility plays a vital role in developing some refereeing skill. Finally they recommend developing agility for improving refereeing skills. Keywords: motor abilities, agility, referees, refereeing skills.